DISCLOSURE REQUIREMENTS FOR ENVIRONMENTAL POLLUTION TO ACHIEVE INFORMATION QUALITY IN THE FINANCIAL STATEMENTS - Mohanad Abed Hussein; Maher Mohammed Abdulkareem; Taleb Hmad Awad (Scholars Digest Publishing, 2024)
This study aims to determine the requirements for disclosing environmental pollution to achieve quality information in financial reports. Disclosure of environmental pollution includes two main sections: The first section includes disclosure of the costs of environmental pollution. The second section deals with disclosure of environmental pollution revenues. Disclosing the costs of environmental pollution includes disclosing information about the environmental costs associated with environmental pollution, and cost management systems associated with environmental pollution. And methods for reducing costs associated with environmental pollution. All information about the costs associated with environmental pollution has an impact on decision makers. Disclosure of environmental pollution revenues also includes all information resulting from revenues generated from the production of products that have a negative impact on environmental pollution, and information related to comparing revenues resulting from environmental pollution activities compared to the negative effects resulting from them. Disclosure of environmental pollution also requires the disclosure of all financial and non-financial information related to environmental costs and revenues. To achieve the goal of the study, Researchers presented problem of study and previous studies related to accounting for environmental pollution. Researchers also presented some previous studies related to achieving quality of financial reports. Researchers focused on the information that cost management tools can provide to reduce environmental costs, and their impact on achieving ecosystem integrity. In order to determine the relationship between the requirements for disclosing environmental pollution and achieving the quality of financial statements. Researchers relied on designing survey list to test study hypothesis, and it distributed into three groups. First group consisted of some employees of companies working in field of environment. Second group consisted of university faculty members. Third group consisted of some employees in accounting & auditing offices. Study hypothesis tested using statistical program SPSS. Study found there is a direct relationship between requirements for disclosing environmental pollution and achieving quality of information in financial reports.
Keywords: Disclosure Requirements, Environmental Pollution, Information Quality.